2015
DOI: 10.3389/fonc.2015.00235
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neutrons in Clinical Proton Therapy

Abstract: In proton therapy, high-energy proton beams cause the production of secondary neutrons. This leads to an unwanted dose contribution, which can be considerable for tissues outside of the target volume regarding the long-term health of cancer patients. Due to the high biological effectiveness of neutrons with regard to cancer induction, small neutron doses can be important. Published comparisons of neutron dose measurements and the corresponding estimates of cancer risk between different treatment modalities dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Fusing protons into boron-11 will release three high LET alpha particles, giving enhancement in effectiveness of proton therapy and causing more damage to the cancerous cells. Another newly proposed method to enhance the radiation effectiveness is Neutron Capture Enhanced Particle Therapy (NCEPT), which uses boron-10 agent to capture the low energy secondary neutrons [22][23][24][25][26] during the proton therapy 9 .…”
mentioning
confidence: 99%
“…Fusing protons into boron-11 will release three high LET alpha particles, giving enhancement in effectiveness of proton therapy and causing more damage to the cancerous cells. Another newly proposed method to enhance the radiation effectiveness is Neutron Capture Enhanced Particle Therapy (NCEPT), which uses boron-10 agent to capture the low energy secondary neutrons [22][23][24][25][26] during the proton therapy 9 .…”
mentioning
confidence: 99%
“…Nevertheless, even if protons reduce the low-dose bath, the conformity of the high-dose region immediately adjacent to the target is superior for IMRT [30]. Moreover, we must keep in mind that the neutron-scattered dose is much higher with 'passive' (scattering) proton technology than with 'active' (pencil beam scanning) proton techniques (PBS-PT) [31]. This PBS PT, particularly intensity-modulated PT, represents the latest advanced PT technology for treating cancers, including thoracic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…[32]. Current risk models used with carefully obtained dose distributions predict a second cancer risk reduction for active protons versus photons, but a more or less constant risk of passive protons versus photons [31], while the potential risks of second cancers from scattered proton RT for childhood cancers may cause concern [33]. On the other hand, a recent prospective randomised comparative trial found no differences between intensity-modulated photon therapy (IMRT) and passive scattering proton RT in patients with non-small cell lung cancer [34], and the dose response (the slope of linear 18 F-FDG-uptake) did not differ significantly between the two modalities [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, to provide a complete description of the cancer-induction risks for a specific RT technique, the dose deposition produced by the different kinds of secondary radiation present during the treatment, which is considered to be of importance for cancer induction, e.g. neutrons, should also be taken into account [27]. We did not calculate the specific risk produced by secondary neutrons in this work.…”
Section: Discussionmentioning
confidence: 99%